Pengaruh lingkungan dan motivasi kerja terhadap kinerja karyawan - Hertina, Dede; Hanafie, Mochammad Handri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to explain the effect of work motivation partially on employee performance, to explain the influence of the work environment partially on employee performance and to explain work motivation and work environment simultaneously on employee performance. Based on the results of the analysis shows that work motivation has a significant effect on the performance of employees of PT. Kemajuan Bangsa, the sampling technique is by using saturated sampling, sampling is a sampling technique when all members of the population are used as samples. The number of samples used in this study were 16 respondents, employees of PT. Kemajuan Bangsa. The data analysis technique in this study was carried out by testing multiple linear regression analysis and classical assumption regression analysis. The results of the study show that the work environment has an effect on employee performance, this can be seen by obtaining the t value (1.603) < t table value (2.14479) and the significance value obtained is 0.135 > 0.05. The t value of the distribution table is sought at a = 5% with degrees of freedom (df) nk or 16-2 = 14, then it is obtained t table = Work environment affects employee performance, this can be seen by obtaining the t value (1.603) < value t table (2.14479) and the significance value can be concluded that the work environment has an influence on employee performance. . The calculated F value and the significance value of this study can be seen in Table 3. From table 3 above, it can be seen that the calculated F value (6.158) is greater than the F table value (3.74), while the significance value is 0.014 <0.05. F table is obtained with df1 = k-1 = 3-1 = 2 and df2 = nk = 36-3 = 33, then the F table value is 3.74. It can be concluded that simultaneously the work environment and motivation variables affect employee performance.